Actitudes hacia el amor: un estudio transcultural entre Ucrania y España - Soriano Ayala, Encarnación; C. Cala, Veronica; Pruska-Pruska, Natalia (國際新教育雜誌, 2023)
This study presents the translation and validation of the Love Attitudes Scale-Short Form (LAS-SF) to the Ukrainian and Spanish context. In addition, a comparative analysis is performed on the love styles shown by a sample of 611 people, of which 346 were residents of the city of Almería (Spain) and 259 were residents of Lviv (Ukraine). The results show good psychometric characteristics for the scale and a factorial invariance between the groups of origin, while preserving the original six-factor structure. Regarding the love styles, similarities are identified between the Spanish and Ukrainians in the importance of ludic (playful) love and the low importance of physical attraction or passionate love. In terms of differences, one can see that ludic, friendly, and pragmatic love styles are significantly higher in the Ukrainian population while obsessive love appears more valued in the Spanish population. Religion is related to significantly diminishing the obsessive love styles. The differences between the Spanish and Ukrainian groups give an account of some of the cultural similarities and differences that exist regarding conceptions of love in the interior of the European continent and that, according to the data, might be related to the role that religion plays in these societies.